2016
DOI: 10.1111/jace.14256
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Absorption of SiC/HfCxN1−x/C Ceramic Nanocomposites with HfCxN1−x‐Carbon Core–Shell Particles

Abstract: The dielectric properties of high‐temperature stable single‐source precursor‐derived SiC/HfCxN1−x/C ceramic nanocomposites are determined by microwave absorption in the X‐band (8.2–12.4 GHz) at room temperature. The samples synthesized at 1700°C, denoted as SiC/5HfCxN1−x/C‐1700°C and SiC/15HfCxN1−x/C‐1700°C ceramics, comprising ≈ 1.3 and ≈ 4.2 vol% HfCxN1−x, respectively, show enhanced microwave absorption capability superior to hafnium‐free SiC/C‐1700°C. The minimum reflection loss of SiC/5HfCxN1−x/C‐1700°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Al 4 SiC 4 and Al 4 Si 2 C 5 are low cost potential materials for high-temperature and weight sensitive applications due to its low density (3.03 g/cm 3 ), high melting point (~2253 K) and excellent oxidation resistance [2][3][4][5]. Both of them have hexagonal structures (P6 3 mc for Al 4 SiC 4 , 3 R m for Al 4 Si 2 C 5 ), and the crystallographic parameters were provided in detail by Inoue et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…Al 4 SiC 4 and Al 4 Si 2 C 5 are low cost potential materials for high-temperature and weight sensitive applications due to its low density (3.03 g/cm 3 ), high melting point (~2253 K) and excellent oxidation resistance [2][3][4][5]. Both of them have hexagonal structures (P6 3 mc for Al 4 SiC 4 , 3 R m for Al 4 Si 2 C 5 ), and the crystallographic parameters were provided in detail by Inoue et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…○ C, and led to dense monolithic HfC x N 1-x /SiC nanocomposites , highlighting homogeneously embedded hafnium carbonitride (HfC 0.83 N 0.17 ) grains in a β-SiC matrix, encapsulated by in situ formed carbon layers. These materials were then characterized in detail regarding their dielectric properties, [188] oxidation resistance, [189][190][191] and laser ablation behavior. [192] HfC x N 1-x /SiC nanocomposites display improved laser ablation resistance compared to pure SiC-based monoliths [192] and are especially suited for electromagnetic shielding in harsh environment.…”
mentioning
confidence: 99%
“…These materials were then characterized in detail regarding their dielectric properties, [188] oxidation resistance, [189][190][191] and laser ablation behavior. [192] HfC x N 1-x /SiC nanocomposites display improved laser ablation resistance compared to pure SiC-based monoliths [192] and are especially suited for electromagnetic shielding in harsh environment. [188,190] It was reported that the additional incorporation of tantalum (Ta) in the HfC x N 1-x phase leads to an enhanced sintering ability of the oxide scale and to an improved oxidation resistance via a short pre-oxidation step at temperatures sufficiently high to activate the formation of silica.…”
mentioning
confidence: 99%
“…Polymer-derived ceramics possess a variety of interesting properties like outstanding thermal stability against decomposition and crystallization, 1)3) excellent high-temperature creep resistance, 4), 5) piezoresistivity at ambient as well as high temperature, 6) high reversible capacity concerning lithium-ion uptake and release 7) and electromagnetic shielding 8) which all rely on the presence of a segregated carbon phase randomly distributed within a glassy matrix.…”
Section: Introductionmentioning
confidence: 99%